Antibacterial Activity of Phyllanthusamarus (Schumand Thonn) Extract against Salmonella Typhicausative Agent Of Typhoid Fever - Dabanka, Christiana Peprah (2014)
A Thesis Submitted to the School of Graduate School, Kwame Nkrumah University Of Science and Technology, in partial fulfilment of the requirements for the award of Master of Science Degree In Environmental Science